Diet of the Omani Owl, Strix butleri, near Nakhal, Oman. Issue 1 (2nd January 2016) - Amr, Zuhair S.; Robb, Magnus S.; Nunes, João M. G.; Abu Baker, Mohammad A.; Walsh, Alyn
Abstract : The diet of the Omani Owl, Strix butleri, was studied for the first time based on re- cently collected pellets. A total of 22 individual prey items represented three mam- mals (all rodents), at least two undetermined gecko species and one scorpion. By fre- quency, Acomys cahirinus constituted 31.8% and lizards 27.3%, while Gerbillus nanus and G. dasyurus were the least consumed prey items (4.5% each).